Enhancement resource scheduling algorithm in LTE-Advanced network with multiple component carriers - Al-Shibly, Mohammed Abuljawad M.; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul; Chebil, Jalel; Zyoud, Al-Hareth (2014)
The LTE-Advanced transmission bandwidth can be expanded by Carrier Aggregation (CA), where CA technology expands effective bandwidth supported to user equipment (UE) by utilizing of radio resources across multiple carriers. This paper proposes novel packet scheduling (PS) condition algorithm that attractively enhances the average system throughput by designing a weighting factor to modified largest weighted delay first PS algorithm. The novel algorithm is implemented in a PS module for LTE-Advanced via system level simulations. The results demonstrate that the effectiveness of Enhanced M-LWDF algorithm in improving throughput.